Comparison of perioperative efficacy and safety between on-pump and off-pump coronary artery bypass grafting in elderly patients - JU Shengjie (Di-san junyi daxue xuebao, 2020)
Objective To compare the efficiency between on- and off-pump coronary artery bypass grafting (CABG) in elderly patients by propensity score matching (PSM). Methods From June 2014 to June 2019, a total of 301 patients (older than 70 years) undergoing CABG in our department were recruited in this study. For 51 patients underwent off-pump CABG (OPCABG), they were 44 males and 7 females, at an age of 70 to 83 (73.31±2.73) years. Another 51 patients including 46 males and 5 females, aged 70-78 (72.82±1.86) years, were selected from the remaining 250 patients treated with on-pump CABG (ONCABG) by PSM. Postoperative recovery was analyzed and compared between the 2 groups. Results There were no statistical differences in the mortality and cases needing intra-aortic balloon pump between the OPCABG and the ONCABG groups. But the former group had shorter endotracheal intubation (10.64±5.07 vs 15.07±5.35 h, P=0.000), less drainage volume at the day after surgery (307.15±132.16 vs 480.78±130.42 mL, P=0.000), and lower percentage of the patients needing continuous renal replacement therapy when compared with the ONCABG group. Conclusion Both OPCABG and the ONCABG surgeries are effective treatment for the elderly patients with coronary heart disease. However, OPCABG is superior to ONCABG in accelerating postoperative recovery and reducing postoperative complications.